Immobilization of enzyme using natural feldspar for use in the synthesis of oleyl oleate - Ali B.J.; Othman S.S.; Rahman M.B.A.; Farah Wahida Harun; Juliana Jumal (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS